Handbook of flexible and stretchable electronics - Hussain, Muhammad Mustafa; El-Atab, Nazek (Boca Raton : CRC Press, 2019)
Flexibility and stretchability of electronics are crucial for next generation electronic devices that involve skin contact sensing and therapeutic actuation. This handbook provides a complete entrée to the field, from solid-state physics to materials chemistry, processing, devices, performance, and reliability testing, and integrated systems development. This work shows how microelectronics, signal processing, and wireless communications in the same circuitry are impacting electronics, healthcare, and energy applications. Key Features: " Covers the fundamentals to device applications, including solid-state and mechanics, chemistry, materials science, characterization techniques, and fabrication; " Offers a comprehensive base of knowledge for moving forward in this field, from foundational research to technology development; " Focuses on processing, characterization, and circuits and systems integration for device applications; " Addresses the basic physical properties and mechanics, as well as the nuts and bolts of reliability and performance analysis; " Discusses various technology applications, from printed electronics to logic and memory devices, sensors, actuators, displays, and energy storage and harvesting. This handbook will serve as the one-stop knowledge base for readership who are interested in flexible and stretchable electronics.
Preface......................................................................................................................vii Editors ....................................................................................................................... ix Contributors ............................................................................................................. xi Section i Fundamentals 1 Plastic Electronics ............................................................................................. 3 Chang-Hyun Kim 2 Materials--Flexible 1D Electronics ................................................................. 23 Aftab M. Hussain 3 Flexible 2D Electronics in Sensors and Bioanalytical Applications .............. 45 Parikshit Sahatiya, Rinky Sha, and Sushmee Badhulika 4 Flexible and Stretchable Thin-Film Transistors ............................................. 63 Joseph B. Andrews, Jorge A. Cardenas, and Aaron D. Franklin 5 Mechanics of Flexible and Stretchable Electronics .........................................91 Nouha Alcheikh Section ii Devices 6 Printed Electronics ..........................................................................................111 Mohammad Vaseem and Atif Shamim 7 Ferroic Materials and Devices for Flexible Memory .....................................149 Saidur R. Bakaul, Mahnaz Islam, and Md. Kawsar Alam 8 Flexible and Stretchable High-Frequency RF Electronics ............................ 165 Juhwan Lee, Inkyu Lee, and Zhenqiang Ma 9 Flexible and Stretchable Sensors ....................................................................189 Tae Hoon Eom and Jeong In Han 10 Artificial Skin .................................................................................................213 Joanna M. Nassar 11 Flexible and Stretchable Actuators ................................................................ 251 Nadeem Qaiser 12 Flexible and Stretchable Photovoltaics and Its Energy Harvesters ............. 277 Devendra Singh 13 Flexible and Stretchable Energy Storage ....................................................... 301 Arwa Kutbee 14 3D Printed Flexible and Stretchable Electronics ........................................... 315 Galo Torres Sevilla 15 Flexible and Stretchable Paper-Based Structures for Electronic Applications ..................................................................................337 Tongfen Liang, Ramendra Kishor Pal, Xiyue Zou, Anna Root, and Aaron D. Mazzeo 16 Reliability Assessment of Low-Temperature ZnO-Based Thin-Film Transistors ......................................................................................................375 Chadwin D. Young, Rodolfo A. Rodriguez-Davila, Pavel Bolshakov, Richard A. Chapman, and Manuel Quevedo-Lopez Section iii Systems and Applications 17 Reconfigurable Electronics ........................................................................... 399 Jhonathan Prieto Rojas 18 Flexible and Stretchable Devices for Human-Machine Interfaces ...............415 Irmandy Wicaksono and Canan Dagdeviren 19 Wearable Electronics ..................................................................................... 467 Sherjeel M. Khan and Muhammad Mustafa Hussain 20 Flexible Electronic Technologies for Implantable Applications .................. 487 Sohail Faizan Shaikh 21 Bioresorbable Electronics .............................................................................. 505 Joong Hoon Lee, Gwan-Jin Ko, Huanyu Cheng, and Suk-Wong Hwang Index .......................................................................................................................525
OCLC-licensed vendor bibliographic record.
Keywords: TECHNOLOGY / Electronics / General; Flexible printed circuits; Semiconductors -- Materials; Electronics -- Materials; Polymers -- Electric properties